2023
DOI: 10.3390/agriculture13040762
|View full text |Cite
|
Sign up to set email alerts
|

Neural Modelling from the Perspective of Selected Statistical Methods on Examples of Agricultural Applications

Abstract: Modelling plays an important role in identifying and solving problems that arise in a number of scientific issues including agriculture. Research in the natural environment is often costly, labour demanding, and, in some cases, impossible to carry out. Hence, there is a need to create and use specific “substitutes” for originals, known in a broad sense as models. Owing to the dynamic development of computer techniques, simulation models, in the form of information technology (IT) systems that support cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…We wanted to test this possibility. MLPs have higher accuracy than RBF networks, but have lower resistance to interference [58][59][60]. As in the previous studies, the generated topologies selected as optimal were ANNs of the MLP type, which indicated the correctness of the model selection.…”
Section: Discussionsupporting
confidence: 66%
“…We wanted to test this possibility. MLPs have higher accuracy than RBF networks, but have lower resistance to interference [58][59][60]. As in the previous studies, the generated topologies selected as optimal were ANNs of the MLP type, which indicated the correctness of the model selection.…”
Section: Discussionsupporting
confidence: 66%
“…In the research described in the first article [8], the authors attempted to find correlations between several selected neural network models and statistical methods commonly used in agriculture. The comparison has a universal dimension-it applies to crop production, livestock production, and the quality of the natural environment.…”
Section: Papers In This Special Issuementioning
confidence: 99%
“…Such difficulties may be overcome, in and efficient and reliable way, by the adoption of Artificial Intelligence (AI) strategies, suitable to mimic neural schemes and to reproduce the behaviour of complex structured systems. In the last decades, AI and, specifically, Artificial Neural Network (ANN) methodology have been successfully applied, with growing interest in various engineering and multidisciplinary research fields, such as structural engineering (see, e.g., [39][40][41][42]), biomedical engineering (see, e.g., [43][44][45]), agricultural engineering (see, e.g., [46][47][48][49]). In particular, in corrugated paperboard research and related applications, ANNs have been employed limited to calibration of mechanical constitutive parameters, [50] estimation of edge crush resistance, [51] evaluation of effects by hand and ventilation holes on box compressive strength.…”
Section: Introductionmentioning
confidence: 99%